(untitled) (International Seven Journal of Multidisciplinary, 2023)
Down syndrome (DS) is a common and complex genetic condition whose effects can manifest in various physiological and behavioral aspects. The most observed effects are in the alterations of the child’s motor and cognitive development in several aspects. Physiologically, respiratory problems are frequent in children with DS and can have several causes, including nasal obstruction, weak thoracic muscles, decreased diaphragm mobility and esophageal function. The objective of this study is to understand physical therapy in home care in children with down syndrome. The methodology used was a literature review research and the articles used were searched in the electronic databases: VHL, Scielo,